K-interpolations in problems of uniform approximation of functions - Pichugov , S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Given an arbitrary metric compactum Q, we compute the K-functional of a pair (C(Q), Cω(Q)) and derive two-sided bounds for (C[−π,π], C2 [−π,π]). We prove interpolation theorems and study applications to problems of the theory of approximation.